Cytohistological correlation in diagnosis of lung tumors by using fiberoptic bronchoscopy: Study of 200 cases - Anita Bodh; Vijay Kaushal; Surender Kashyap; Anchna Gulati (Wolters Kluwer Medknow Publications, 2013)
Background: Examination of specimens obtained through flexible fiberoptic bronchoscope is an important and often the initial diagnostic technique performed in patients with suspected malignant lung lesion. Aims: To evaluate the correlation of cytological findings of bronchial washings, bronchial brushing and imprint smear of bronchial biopsy in the diagnosis of lung tumors, with histopathology of bronchial biopsy taking the latter as the confirmatory diagnostic test. Materials and Methods: A total of 200 patients with lung mass were included in the study. Bronchial brushings were obtained from all 200 cases. In the first 100 cases, pre-biopsy bronchial washing (washing collected before the brushing and biopsy procedure) while post-biopsy washing (washing at the end of the procedure) was procured in all 200 cases. Imprint smears of bronchial biopsy were prepared in 150 cases. Results: Sensitivity and specificity of brushing was 76.58% and 77.78% respectively and that of imprint smear was 81.35% and 78.12% respectively. Pre-biopsy and post-biopsy washing showed high specificity of 88.89%, but low sensitivity of 30.14 and 36.77% respectively. No significant difference was found in sensitivity between brushing and imprint smear (Chi-square; P = 0.4187); and between pre-biopsy and post-biopsy washing (Chi-square; P = 0.7982). However, there was a significant difference between sensitivity of brushing and washing (Chi-square; P = 0.0001). The sensitivity of combination of three cytological diagnostic techniques was 87.29%. Conclusion: Bronchial brushing and washing cytology in combination with imprint cytology aids in the diagnosis of lung tumors. Therefore, all these techniques may be used concurrently along with bronchial biopsy to diagnose lung tumors.